Developing and Creating Board Game as a Media to Learn English Vocabulary for Senior High Student - Kevin Christopher; Bernardus Harnadi; Hendra Prasetya (Journal of Business and Technology, 2021)
Students have a general problem to even start learning the English language. Through the game, student will only feel that they’re playing games and not studying, increasing the willingness of someone to learn more by averting their mindset to think that they are playing instead of studying. The game will be created in a form of a board game, the reason is the game is seen as more a friendly and more acceptable by more people. The objective of this research is to design a board game helping student to increase their English proficiency in a friendlier, easier, and enjoyable manner. The board game was tested to 40 students on high school by letting them play it 10 times in different day each time they play, and then filling the questionnaire. The questionnaire then will be processed in SPSS software to conclude the result of the research. This research will produce an English learning educational board game which will improve their English proficiency in a fun and cooperative way (togetherness).